2015
DOI: 10.1007/s10965-015-0835-y
|View full text |Cite
|
Sign up to set email alerts
|

Vinylic copolymerization of norbornene and higher 1-alkene with three-dimensional geometry binickel catalyst

Abstract: Compared with monometallic complex, the threedimensional geometry α-diimine binickel complex exhibited higher activities (5.5×10 5 -2.7×10 7 g polymer /mol Ni ·h) in the homopolymerization of norbornene and copolymerization of norbornene with 1-hexene or 1-decene in the presence of B(C 6 F 5 ) 3 . The 1-hexene or 1-decene content in the copolymers could be controlled up to 9.2-25.3 % or 8.8-17.8 % by varying the comonomer feed ratios 1-hexene or 1-decene from 10 to 50 %. It was observed that the yield depended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Alkylaluminium is usually used as cocatalyst in organometallic catalytic systems for alkylation and removing impurities, and organoboron compounds are extensively applied in the polymerization of NBE to form a cationic active center . Therefore, complex 1 , TIBA and B were chosen as components of the ternary catalytic system for the homopolymerization of NBE.…”
Section: Resultsmentioning
confidence: 99%
“…Alkylaluminium is usually used as cocatalyst in organometallic catalytic systems for alkylation and removing impurities, and organoboron compounds are extensively applied in the polymerization of NBE to form a cationic active center . Therefore, complex 1 , TIBA and B were chosen as components of the ternary catalytic system for the homopolymerization of NBE.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of cycloolefin copolymers (COCs), commercially produced via copolymerization of N with ethylene (E), can be easily controlled by comonomer content and sequence distribution 6–8. Copolymerization of N with higher 1‐alkenes was also reported to modify the physical properties 9,10. To reduce the birefringence of PNB with controlled T g value, some research groups including us reported the incorporation of styrene (S) into PNB main chain by copolymerizing N and S 11–13.…”
Section: Introductionmentioning
confidence: 99%
“…However, the further development of norbornene is hampered by its poor bond properties, low solubility and poor mechanical properties. At present, the introduction of polar groups [18][19][20] or exible chains [21][22][23][24][25] on the norbornene backbone is the most effective means to solve this problem. In order to achieve this goal, it is important to synthesize some efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Norbornene is a typical cycloolen with many advantages of cycloolens, but due to the presence of bicyclic skeletons in the polymer, it is brittle and has a small elongation at break. In order to improve its defects, the copolymer obtained by copolymerizing norbornene with a-olen 22,23,36 not only can reserve the heat resistance and dimensional stability of polynorbornene, but also has excellent optical properties, good processing and solubility, which has attracted scholars's attention at both home and abroad. For example, Kaminsky group 37 achieved the copolymerization of norbornene with ethylene using a metallocene catalyst.…”
Section: Introductionmentioning
confidence: 99%